An unusual reason for an inguinal swelling: De Garengeot's hernia. Issue 3 (22nd March 2021) - Sommerhalder, Barbara; Burger, Reint; Bueter, Marco; Thalheimer, Andreas
Abstract: We present the case of a 71-year-old female with an inguinal swelling. Intra-abdominally the appendix was found in a femoral hernia sac (De Garengeot's hernia). A laparoscopic transabdominal preperitoneal hernia repair procedure was performed with uneventful post-operative course. Clinical presentation of this type of hernia is unspecific and often not to be distinguished from a common incarcerated hernia. Computed tomography can be helpful in obtaining a diagnosis, although the definite diagnosis is mostly found intraoperatively. As surgical options are numerous, there is no consensus on the most suitable one. A laparoscopic approach incorporates the benefit of a total abdominal overview and the possibility of standard procedures. If the appendix appears normal, the use of synthetic mesh is considered safe and an incidental appendectomy is not necessarily required.